Concentration of some trace elements in gills, liver and muscles of two species of fish in Al-Dwaniya river - Haider M. Hussein; Basim Y. Al-khafaji (Al-Qadisiyah Journal of Pure Science, 2017)
The current study was conducted to determine the concentration of five trace elements)Cd, Cu, Ni, Pb and Zn) in gill, liver and muscles of two species of fish Cyprinus carpio and Tilapia zilli ). from May(summer) 2013 up to April(spring) 2014 from three sites from Al-Diwaniya river.The concentrations of trace elements (cadmium, copper, nickel, lead and zinc) in two species of fish in Al-Diwaniya river ranged according to organs in gills of Cyprinus carpio ranged from(0.63 – 2.07))3.19 -3.90), )4.04– 8.96) ,(1.95 - 3.76), )182.14 - 253.89) μg/g dry weight respectively, in liver from(0.41-1.78) , (6.20 - 32.47 ),(5.97- 10.39),(2.06-5.37), (136.15 - 184.75) μg/g dry weight respectively, and in muscles from(0.49-3.43ك),(2.82 - 10.40),(7.17-11.57 ),( 0.61- 4.60 ),( 110.96- 160.46) μg/g dry weight respectively. and ranged in Tilapia zilli in gills from(0.44 - 1.15),( 1.06-6.83),(8.18 -13.97 ),(1.46 - 2.89) ,(99.03 - 155.33) μg/g dry weight respectively, in liver from(0.57-1.64 ),(13.08-28.06),( 8.03-18.50), (1.32- 3.02),(112.68 - 176.32) μg/g dry weight respectively, and in muscles(0.46-1.80), (2.42 - 2.93),(7.47-10.52),( 0.20 -3.16 ),( 79.74-153.58(μg/g dry weight respectively. And in the organs of fish was follow in Cyprinus carpio: gills> liver>muscle,while in Tilapia zilli was follow liver > gills >muscle.